PREVENTIVE MAINTENANCE OF AIR HEATER ON BOILER UNITS 1- 4 AT PT. PLN INDONESIA POWE SURALAYA PGU - Putra, Styven Handoyo; Notonegoro, Hamdan Akbar; Saefuloh, Iman; Wahyudi, Hadi; Sudrajad, Agung; Alhamidi, A. Ali (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
One of the components used in power plants in boilers is the water heater. Of course, it has a very important role in the power plant. Its function is that it is very tight in the steam power plant, making the air heater work 24 hours, so its use is quite important. Knowing the function and usefulness of the Air Heater is important enough to require proper preventive. PT. Indonesia Power Suralaya PGU applies very strict Maintenance because of the losses experienced if the plant has damage which causes the unit to be forced to stop then the loss experienced is also very large. Preventive Maintenance performed on the Air Heater is done by looking at the condition visually and sound as the cornerstone of the repair analysis so that the treatment effort can be done well in terms of tightening, lubricating, and cleaning 32 minutes is the effective time an inspection is carried out whether there is significant damage or not. At the PM in the Air Heater found the effective run time every day is 2 hours 59 minutes when no indication of damage is found.